Determinan Keuntungan Bagi Hasil Dengan Penguatan Dana Pihak Ketiga Pada Bank Umum Syariah - Astuti, Widya; Abdullah, Muhammad Wahyuddin; Trimulato (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2023)
This study aims to describe the Determinants of Profit Sharing by Strengthening Third Party Funds at Islamic Commercial Banks in Indonesia. The population and sample used in this study are Islamic Commercial Banks in Indonesia registered with the Financial Services Authority (OJK) in 2015-2020. This research is a type of quantitative research using multiple linear regression analysis and moderated regression analysis (MRA). The source of data used in this research is secondary data, which has been presented by certain institutions. The data collection technique used was purposive sampling in determining the sample. The data analysis technique used is descriptive quantitative using the SPSS application. The results of the study state that mudharabah financing has a negative effect on profit sharing, musyarakah financing has a positive effect on profit sharing, ijarah financing has a positive effect on profit sharing, third party funds (DPK) cannot strengthen the effect of mudharabah financing on profit sharing, third party funds Third party funds (DPK) can strengthen the effect of musharaka financing on profit sharing, and third party funds (DPK) cannot strengthen the effect of ijarah financing on profit sharing.